2005
DOI: 10.1523/jneurosci.1084-05.2005
|View full text |Cite
|
Sign up to set email alerts
|

Neural Basis for a Powerful Static Motion Illusion

Abstract: Most people see movement in Figure 1, although the image is static. Motion is seen from black 3 blue 3 white 3 yellow 3 black. Many hypotheses for the illusory motion have been proposed, although none have been tested physiologically. We found that the illusion works well even if it is achromatic: yellow is replaced with light gray, and blue is replaced with dark gray. We show that the critical feature for inducing illusory motion is the luminance relationship of the static elements. Illusory motion is seen fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
91
3
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(100 citation statements)
references
References 22 publications
5
91
3
1
Order By: Relevance
“…A nonmutually exclusive possibility is that microsaccades may displace after-images caused by the black and white stripes in the pattern and thus cause phi movement. Conway and coworkers (61,63) recently showed that pairs of stimuli of different contrasts can generate motion signals (i.e., phi movement) in directionally selective neurons of areas V1 and MT, and proposed that this neural mechanism may underlie the perception of another type of illusory motion from static patterns (61)(62)(63). Whatever neural circuit is responsible for the percept, the link between microsaccades and the generation of illusory motion signals has not been directly demonstrated until now.…”
Section: Effect Of Microsaccades In the Perception Of Illusory Motionmentioning
confidence: 99%
“…A nonmutually exclusive possibility is that microsaccades may displace after-images caused by the black and white stripes in the pattern and thus cause phi movement. Conway and coworkers (61,63) recently showed that pairs of stimuli of different contrasts can generate motion signals (i.e., phi movement) in directionally selective neurons of areas V1 and MT, and proposed that this neural mechanism may underlie the perception of another type of illusory motion from static patterns (61)(62)(63). Whatever neural circuit is responsible for the percept, the link between microsaccades and the generation of illusory motion signals has not been directly demonstrated until now.…”
Section: Effect Of Microsaccades In the Perception Of Illusory Motionmentioning
confidence: 99%
“…This illusion is called the Rotating Snakes illusion and can be considered an optimized version of either the Fraser-Wilcox illusion (Fraser & Wilcox, 1979;Naor-Raz & Sekuler, 2000) or the peripheral drift illusion (Faubert & Herbert, 1999). Conway et al (2005) suggested that these responses occur in the neurons in MT (middle temporal) and Kuriki et al (2008) showed that in humans hMT+ (middle temporal complex) responds to this illusion. Moreover, Ashida et al (2012) showed evidence that V1 (primary visual cortex) -V4, V3A (V3 accessory), and MT+ are involved in this illusion.…”
Section: Introductionmentioning
confidence: 99%
“…1E) (Kitaoka, 2005). A grayscale version of the illusion is effective perceptually as well, and drives the responses of directionally selective visual neurons, so long as the luminance relationship between the patches is preserved (Conway et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The Rotating Snakes is a spatiotemporal illusion, in which both spatial layout and temporal stimulation-usually brought about by eye movements (Backus and Oruç, 2005;Conway et al, 2005;Murakami et al, 2006;Beer et al, 2008;Ashida et al, 2010)-are critical to the perception. The specific eye movements and neural mechanisms involved remain controversial, however.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation